مدى توفر معايير التوجيه الإسلامي في محتوى مناهج العلوم بالمرحلة المتوسطة بالمملكة العربية السعودية - غامدي، عبد الله سعيد أحمد (Kulliyyah of Education, International Islamic University Malaysia, 2015)
This study aimed to determine the main objectives of science education in Islam which achieve the Integration of knowledge, and obtain a list of standards for the content of science education in Islam from these objectives. Further, to examine the availability of these standards in the science curriculum content of the intermediate stage in Saudi Arabia. The researcher used descriptive analytical method based on content analysis method to describe and identify a list of objectives and a list of standards followed by designing the study instrument for the analysis of the all syllabus content included in science books in intermediate stage for the academic year (1433/1434 AH). The researcher used frequency and percentages to determine the availability of these standards in the content of the curriculum. The most important results of the study showed seven general objectives to achieve Integration of Knowledge in science education in Islam. The standards for Islamic guidance of science curricula content-derived of these goals are six key criterion and (34) sub-standards. These standards reached a medium rate a percentage of 61.4%, in science curriculum content in intermediate stage in Saudi Arabia. However, the content of these curricula is rich with the scientific knowledge, which does not violate the Islamic perceptions. But it is weak in strengthening the Islamic doctrine and developing the faith of Allah. That is because the content of these curriculum are affected by the philosophy of American material pragmatism, where the content of this curriculum is originally an American curriculum, was adopted and aligned with the Saudi setting. These curriculum are achieving the educational policy in the Kingdom of Saudi Arabia on the principle of scientific knowledge. However, neglecting the principle of faith, which is the basis of the education. The study concluded with some recommendations and suggestions, and the most important of them is the modifications that the researcher suggested to be in the content of these curricula based on this evaluation to achieve the general aims of science education in Islam.